(untitled) (Bangladesh Journal of Livestock Research, 2016)
This experiment estimated the selection responses for egg production of Fayoumi (Fay) and Rhode Island Red (RIR) breeds. A total of 3000; belonging Fay 2000 & RIR 1000 day old chicks were collected from Egypt and Bangladesh Livestock Research Institute (BLRI), Savar, Dhaka respectively, considered as foundation stock. The chicks were brooded for 5 weeks and reared up to 14 weeks of age providing standard feeding and management. After brooding, 640 Fay and 504 RIR pullets were reared in 40 and 36 individual pens respectively, considering as a family. Finally, 30 and 24 best families of Fay and RIR respectively were selected with 420 Fay and 288 RIR pullets at 15 weeks of age, on the basis of age at 1st egg lay, egg production and fertility. Salmonella and mycoplasma free eggs were collected on the basis of blood test (agglutinate test) from the selected families of both the breeds and hatched out for next generation. The experiment was continued up to 40 weeks of age for each generation. The study revealed that hen day egg production of Fay and RIR was higher in Foundation stock (64.39% in Fay and 68.54% in RIR) than that of F1 generation (58.6% in Fay and 46.8% in RIR) but no significant difference (P > 0.05) was observed for livability between Foundation stock and F1 generation. Reasons for lower productivity in F1 generation may be the poor management practices during growing period. In F2 generation, egg production was higher in both the breeds (64.09% in Fay and 62.05% in RIR) than in F1 generation. Egg production of RIR was not recorded for F3 generation, as their ability to adopt under farmers condition was very poor. However, in F3 generation, egg production of Fay was higher (65.82%) than in F2 generation. Genetic gain in Fay was 0.06%, 0.11% and 0.12% for F1, F2 and F3 generation, respectively. In case of RIR genetic gain was 0.07% in F1 and 0.18% in F2 generation. Due to selection slight genetic gain for egg production was obtained in Fay and RIR but further research with larger stock is needed for better understanding of selection responses of these breeds. Bangladesh J. of Livestock Res. 19(1-2): 66-73, Jan-Dec 2012